The Effect of population growth on the economic growth of 43 Sub-Saharan African countries - TESSEMA, Henok Fantahun (KDI School, 2022)
Africa is expected to contribute more than half of the global demographic expansion between now and 2050. By 2050, Sub-Saharan Africa’s population is predicted to double. According to the World Bank, recent drops in the birth rate in Sub-Saharan Africa imply that the working ages (25 to 64 years) population is rising more rapidly than those of different age groups, increasing the likelihood of economic expansion. Using a panel data methodology, the paper investigates the effect of demographic expansion on the economy of 43 Sub-Saharan African countries from 1990 to 2019. The analysis employed annual secondary data from the database of development indicators of the World Bank and from the database of world economic outlook of IMF. Besides the analysis of descriptive statistics, panel model of random and fixed effects have been used to observe the data. The results of both models of fixed and random effects analysis revealed a one-to-one correlation between GDP per capita growth and population surge, suggesting that demographic expansion benefits the economy. The study recommends that Sub-Saharan African countries design and execute realistic population policy initiatives to increase the productivity level of their population to reap larger demographic dividend gains.
Thesis(Master) -- KDI School: Master of Public Management, 2022
Keywords: Population--Economic aspects--Africa, Sub-Saharan; Economic development--Africa, Sub-Saharan